Over here, over there : transatlantic conversations on the music of World War I - Brooks, William, 1943-; Bashford, Christina; Magee, Gayle Sherwood, 1965- (Urbana, Illinois : University of Illinois Press, 2019)
"During the Great War, composers and performers created music that expressed common sentiments like patriotism, grief, and anxiety. Yet music also revealed the complexities of the partnership between France, Great Britain, Canada, and the United States. At times, music reaffirmed a commitment to the shared wartime mission. At other times, it reflected conflicting views about the war from one nation to another or within a single nation. Over Here, Over There examines how composition, performance, publication, recording, censorship, and policy shaped the Atlantic allies' musical response to the war. The first section of the collection offers studies of individuals. The second concentrates on communities, whether local, transnational, or on the spectrum in-between. Essay topics range from the sinking of the Lusitania through transformations of the entertainment industry to the influenza pandemic. Contributors: Christina Bashford, William Brooks, Deniz Ertan, Barbara L. Kelly, Kendra Preston Leonard, Gayle Magee, Jeffrey Magee, Michelle Meinhart, Brian C. Thompson, and Patrick Warfield"--
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on October 28, 2019).
eBooks on EBSCOhost
Keywords: Music -- Social aspects -- United States -- History -- 20th century; World War, 1914-1918 -- Music and the war; Music and war -- Europe -- 20th century; Music and war -- United States -- 20th century; Musique -- Aspect social -- États-Unis -- Histoire -- 20e siècle.; Musique et guerre -- Europe -- 20e siècle.; Musique et guerre -- États-Unis -- 20e siècle.; MUSIC -- General; Music -- Social aspects; Music and war; Europe; United States; 1900-1999; Electronic books; History